Osteoporosis and Impaired Trabecular Bone Score in Hemodialysis Patients - Brunerová, Ludmila; Ronová, Petra; Verešová, Jana; Beranová, Petra; Potoèková, Jana; Kasalický, Petr; Rychlík, Ivan (Kidney & blood pressure research, 2016)
BACKGROUND/AIMS: Small attention is paid to other types of bone diseases then chronic kidney disease-mineral and bone disorder in dialysis patients. The aim of our study was to assess the occurrence of osteoporosis and bone microarchitecture by trabecular bone score in this population. METHODS: 59 patients (67.6 ± 13.1 years, 43 males) treated with hemodiafIltration underwent densitometry (Lunar Prodigy, TBS software 2.1.2) and laboratory assessment. RESULTS: Osteoporosis was observed in 34% patients, high bone turnover was found in 80% of them, with SHPT (PTH > 300 ng/l) present in 69%. TBS was significantly decreased in 47.5% of the patients. TBS correlated with T- and Z-scores of the lumbar spine and proximal femur in the total population (P < 0.0001) and in men (P < 0.00001) and there were significant differences between TBS in groups with normal densitometry, osteopenia, and osteoporosis, both in total population (P < 0.0001; P < 0.01) and in men (P < 0.001; P < 0.001). CONCLUSIONS: Osteoporosis was found in about 1/3 of patients treated with hemodiafiltration. Normal TBS was found in only 1/4 of the dialysis population. TBS correlated with densitometric parameters and was significantly different relative to T-scores.
Keywords: Humans; lidé středního věku; nemoci ledvin; trabekulární kostní tkáň; osteoporóza; Renal Dialysis; Female; Aged; dialýza ledvin; senioři; lidé; Densitometry; minerálová a kostní nemoc při chronickém onemocnění ledvin; ženské pohlaví; Male; Middle Aged; Bone Density; Aged, 80 and over; kostní denzita; senioři nad 80 let; Cancellous Bone; denzitometrie; Osteoporosis; mužské pohlaví; Chronic Kidney Disease-Mineral and Bone Disorder; Kidney Diseases